2011
DOI: 10.1287/mnsc.1100.1255
|View full text |Cite
|
Sign up to set email alerts
|

Competing to Be Certain (But Wrong): Market Dynamics and Excessive Confidence in Judgment

Abstract: In this paper, we investigate how market competition contributes to the expression of overconfidence among those competing for influence. We find evidence that market competition exacerbates the tendency to express excessive confidence. This evidence comes from experiments in which advisors attempt to sell their advice. In the first, advisors must compete with other advice sellers. In the second, advisors and their customers are paired. Advisors are overconfident in both studies and it helps advisors sell thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 36 publications
0
71
1
Order By: Relevance
“…The current research examines one possible reason why: by systematically promoting highly confident and overconfident individuals into positions of power, groups might in some cases hamper their collective performance. Second, we extend emerging research on the interpersonal consequences of confidence and overconfidence (e.g., Anderson, Brion, Moore, & Kennedy, 2012;Radzevick & Moore, 2011;von Hippel & Trivers, 2011). While prior work has emphasized the interpersonal benefits of overconfidence for the individual, here we examine whether overconfidence can incur costs to the collective.…”
Section: Contributionsmentioning
confidence: 89%
“…The current research examines one possible reason why: by systematically promoting highly confident and overconfident individuals into positions of power, groups might in some cases hamper their collective performance. Second, we extend emerging research on the interpersonal consequences of confidence and overconfidence (e.g., Anderson, Brion, Moore, & Kennedy, 2012;Radzevick & Moore, 2011;von Hippel & Trivers, 2011). While prior work has emphasized the interpersonal benefits of overconfidence for the individual, here we examine whether overconfidence can incur costs to the collective.…”
Section: Contributionsmentioning
confidence: 89%
“…With the rise of performance management and measurement in the public sector, numbers as an independent object of study enter the stage (Hood, 2007;Moynihan, 2008), or as Radin notes, "There is perhaps no element within the performance measurement process that is more important than the reliance on numbers and quantitative presentation of accomplishments" (2006, p. 27). Some have suggested that politicians might benefit from inflating their stated confidence about numbers (Wildavsky, 1964;Radzevick & Moore, 2011). Recent research suggests that one way of increasing citizens' confidence in numbers is by using more precise numbers (Janiszewski & Uy, 2008;Thomas et al, 2010;Mason et al, 2013;Jerez-Fernandez et al, 2014;Zhang & Schwarz, 2013).…”
mentioning
confidence: 99%
“…In political-administrative settings, politicians and managers are the producers of numbers while citizens are the potential receivers (Yanic & Foster, 1995, 1997Radzevick & Moore, 2011). If individuals prefer precise estimates, then number producers have strong incentives to supply precision (Radzevick & Moore, 2011;Jerez-Fernandez et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ironically, however, people are less motivated to seek out performance information when advisors are confident, making confidence a double-threat (Sah, Moore, & MacCoun, 2013). In fact, even when performance feedback shows that two advisors are equally accurate, people prefer the more confident advisor, despite being aware that the advisor's confidence is higher than is warranted (Price & Stone, 2004;Radzevick & Moore , 2011).…”
Section: Social Benefitsmentioning
confidence: 99%